Convergent DNA synthesis: a non-enzymatic dimerization approach to circular oligodeoxynucleotides. - Rubin, E (1995)
We report a novel convergent approach to the construction of circular DNA oligonucleotides from two smaller linear precursors. Circular DNAs 34-74 nucleotides (nt) in size are constructed non-enzymatically in a single step from two half-length oligomers. A DNA template is used to assemble the constituent parts into a triple helical complex which brings the four reactive ends together for chemical ligation with BrCN/imidazole/Ni2+. A homodimerization reaction strategy is successfully used on a small scale to construct circles 42, 58 and 74 nt in size. In addition, a heterodimerization strategy is successfully used in two cases to construct circular 34mers from different 16mer and 18mer precursors. Measurement of preparative yields for one biologically active 34mer circle shows that the dimerization strategy gives a yield higher than that from conventional cyclization and nearly as high as that for a normally synthesized linear DNA, establishing that there is not necessarily a yield penalty for circle construction. Six additional preparative circle constructions, giving conversions of approximately 33-85% from precursors to circular product, are also described. Convergent strategies allow the construction of medium and large size DNA molecules in higher yields than can be achieved by standard linear synthesis alone.